Patrones de asentamiento, rutas de comunicación y mercancías de intercambio a larga distancia en el Formativo Tardío del Austro Ecuatoriano - Karen Olsen Bruhns (Bulletin de l'Institut Français d'Études Andines, 2010)
On the basis of current evidence it would appear that the Formative Period was delayed in the southern sierra of Ecuador. With the rise of the Chorrera culture, whose emergent elites had a need for exotic goods, we see the beginnings of ceramics, agriculture and, somewhat later, camelid pastoralism. From the modern provinces of Azuay and Cañar we have evidence of small villages, located in various ecological zones, and often on major routes of communication. These villages maintained a high degree of contact among themselves, but also were entering into trade with the coast and the tropical forest to the east, presumably via routes which are largely still in use. The investigation of the materials involved in this trade has hardly begun, but sea shells, ceramics, cinnabar, rock crystal, colored hard stones, metals and probably perishable materials such as textiles of camelid wool were involved. Long distance Exchange also functioned as a means to comunicate ideas and technologies.